A cross-sectional survey to ascertain the prevalence of oral habits among eleven to twelve year old children in Trinidad and Tobago. Issue 2 (August 2020) - Hoyte, Trudee A.; Ali, Anil; Bearn, David R.
Abstract: Objective: The aim of this study was to determine the prevalence of oral habits in eleven to twelve year old children in Trinidad and Tobago and to determine if there is any association with ethnicity and gender. Design: Cross-sectional survey. Methods: An epidemiological survey of 975 high school students (566 females (58.1%) and 409 males (41.9%)) was conducted. A questionnaire was developed to record information on the presence of oral habits. A clinical examination was also conducted at the school site. Statistical analysis was undertaken using Chi-square test and binary logistic regression. Results: There was a high prevalence of oral habits. The overall prevalence of habits was 93%. 81.3% of children had a tongue thrust, 46.3% nail biting habit, and 34.9% digit sucking habit. Afro-Trinidadian subjects and female subjects were more likely to have habits with tongue sucking in particular exhibiting a female (OR 0.419 95%CI 0.285, 0.616) and Afro-Trinidadian ethnic (OR 0.559 95%Ci 0.433, 0.721) predilection. Conclusion: The prevalence of oral habits in eleven and twelve year old children in Trinidad and Tobago is high, with higher prevalence in females and Afro-Trinidadians with tongue thrusting being most prevalent oral habit overall.